(untitled) (Research, Society and Development, 2024)
The discussion about nutrition and health and the abundance of information make it essential to develop skills for making healthy dietary choices. This paper aims to show the influence of fad diets on health and their prominence on social media and other media platforms. It is a literature review based on scientific and bibliographic articles from PUBMED, Google Scholar, and SciELO, using descriptors such as "Fad Diets," "Behavioral Nutrition," "Nutrition Sciences," and "Nutritional Education. The main articles indicate that these diets are popular among women, often due to dissatisfaction with body image. Guidance from a nutritionist is crucial to avoid mental and physical health issues. The study reveals that these diets are ineffective in the long term, with only 15.4% of participants maintaining weight loss after one year. However, most participants rate the short-term results positively. Diets promoted on social media can be harmful, promising quick changes and body transformations to resemble influencers, celebrities, and models. Examples include detox diets, which claim to eliminate toxins and aid in weight loss, and low-calorie diets, recommended for short periods with medical supervision. It is concluded that nutritional guidance is essential to avoid health issues and ensure lasting results.